Molecular dynamics simulation links conformation of a pore-flanking region to hyperekplexia-related dysfunction of the inhibitory glycine receptor - Breitinger, Hans-Georg Albrecht; Lanig, Harald; Breitinger, Ulrike; Clark, Timothy; et al. (Chemistry & Biology, 2004)
Inhibitory glycine receptors mediate rapid synaptic inhibition in mammalian spinal cord and brainstem. The previously identified hyperekplexia mutation GLRA I(P250T), located within the intracellular TM1-2 loop of the GlyR alpha1 subunit, results in altered receptor activation and desensitization. Here, elementary steps of ion channel function of alpha1(250) mutants were resolved and shown to correlate with hydropathy and molar volume of residue alpha1 (250). Single-channel recordings and rapid activation kinetic studies using laser pulse photolysis showed reduced conductance but similar open probability of alpha1 (P250T) mutant channels. Molecular dynamics simulation of a helix-turn-helix motif representing the intracellular TM1-2 domain revealed alterations in backbone conformation, indicating an increased flexibility in these mutants that paralleled changes in elementary steps of channel function. Thus, the architecture of the TM1-2 loop is a critical determinant of ion channel conductance and receptor desensitization.